KEDUDUKAN NOTARIS YANG MEMILIKI JABATAN STRUKTURAL DI PERGURUAN TINGGI - Roosalina Kartini; Rusdianto Sesung (Al-Adl : Jurnal Hukum, 2019)
AbstractCharacteristic of Notarial as an esoteric science brings consequence which makes this science cannot be taught to person who does not possess knowledge within this field.  In order to produce high quality candidates of notary public, Some University as educational agency of notarial science provides structural position for notarial practitioner to become lecturer in Notarial Master Program at the University. This approach is conducted to adjust between learning curriculum of notarial science and learning outcome of the graduates as notary public. But this approach is obstructed with rules that are enacted in Regulation of Notary Public (Undang-Undang Jabatan Notaris) which prohibit notary public to hold double positions as lecturer coupled with practitioner. Keywords: Notary Public, Double Positions, Structural Position. AbstrakKarakteristik ilmu Kenotariatan sebagai ilmu yang esoterik membawa konsekuensi bahwa ilmu tersebut tidak bisa diajarkan oleh orang yang tidak memahami seluk beluk dunia kenotariatan. Demi menghasilkan calon Notaris yang berkualitas beberapa Perguruan Tinggi penyelenggara program Magister Kenotariatan memberikan jabatan struktural kepada praktisi Notaris yang menjadi Dosen pengajar di Perguruan Tinggi tersebut agar mampu menyesuaikan kurikulum pembelajaran dengan kebutuhan praktek nantinya. Kondisi tersebut dihadapkan dengan ketentuan dalam Undang-Undang Jabatan Notaris yang mengatur larangan rangkap Jabatan Notaris. Kata kunci : Notaris, Rangkan Jabatan, Jabatan Struktural